Growth and Productivity of Antarctic Sea Ice Algae under PAR and UV Irradiances - McMinn, A; Ashworth, CM; Ryan, K (Botanica Marina, 1999)
A light perturbation experiment on sea ice at Cape Evans in 1996 found significant differences in biomass accumulation between ice algal assemblages exposed to additional UVB, UVA and PAR irradiances and those exposed to either control or elevated PAR and UVA without UVB. Sea ice with its snow cover removed (and thus exposed to additional UVB, UVA and PAR) had a 40% lower rate of biomass accumulation than sea ice with its snow cover removed but covered with UVB-absorbing mylar. Chlorophyll-specific production under PAR was up to 0.05 mg C (mg Chl a)-1 h-1 although it was approximately 0.02 mg C (mg Chl a)-1 h-1 at ambient under ice irradiances of 2-6 mol photons m-2 s-1 PAR. UVB irradiation was found to have a greater impact on highly shade-adapted sea ice algal communities beneath thick ice with a thick snow cover than on thinner ice with less snow.